RE CERTAIN LAWS OF MAGNETIC DISTURBANCE IN THE HIGH LATITUDES - Burdo,O. A. (1959)
In the high latitudes, there are no persistent magnetic storm phenomena of any importance that are unrelated to the irregular fluctuations. In each individual case of magnetic disturbance, there develops a system of superficial horizontal currents extending over the whole polar cap and similar in form to the mean current system. There are three spiral bands in which the current density exhibits maximum values. The dynamo effect in the ionosphere seems the most likely cause of the magnetic disturbances. The dynamo theory provides a natural and simple explanation for the principal observed laws. (Author) Trans. of mono. Fizika Solnechnykh Korpuskulyarnykh Potokov i Ikh Vozdeistvie na Verkhnyuyu Atmosferu Zemli, Moscow, 1957, p. 159-166, 174-177. (Conference Committee on Solar Research, 22 Nov 55. Transactions.) Also available from NRC as C-3167.